Spectroscopic Studies on Nicotine and Nornicotine in the UV Region1. Issue 5 (14th March 2013) - Clayton, Peter M.; Vas, Carl A.; Bui, Tam T.T.; Drake, Alex F.; McAdam, Kevin
ABSTRACT The UV absorption and electronic circular dichroism (ECD) spectra of (R)‐ and (S)‐nicotine and (S)‐nornicotine in aqueous solution were measured to a significantly lower wavelength range than previously reported, allowing the identification of four previously unobserved electronic transitions. The ECD spectra of the two enantiomers of nicotine were equal in magnitude and opposite in sign, while the UV absorption spectra were coincidental. In line with previous observations, (S)‐nicotine exhibited a negative cotton effect centered on 263 nm with vibronic structure (π–π1* transition) and a broad, positive ECD signal at around 240 nm associated with the n–π1* transition. As expected this band disappeared when the pyridyl aromatic moiety was protonated. Four further electronic transitions are reported between 215 and 180 nm; it is proposed the negative maxima around 206 nm is either an n–σ* transition or a charge transfer band resulting from the movement of charge from the pyrrolidyl N lone pair to the pyridyl π* orbital. The pyridyl π–π2* transition may be contained within the negative ECD signal envelope at around 200 nm. Another negative maximum at 188 nm is thought to be the pyridyl π–π3* transition, while the lowest wavelength end‐absorption and positive ECD may be associated with the π–π4* transition. The UV absorption spectra of (S)‐nornicotine was similar to that of (S)‐nicotine in the range 280–220 nm and acidification of the aqueous solution enhanced the absorption. The ECD signals of (S)‐nornicotine were considerably less intense compared to (S)‐nicotine and declined further on acidification; in the far UV region the ECD spectra diverge considerably. Chirality 25:288–293, 2013. © 2013 Wiley Periodicals, Inc.